Computational Investigation of Flow Control Methods in the Impeller Rear Cavity. (22nd February 2020) - Liu, Guang; Du, Qiang; Liu, Jun; Wang, Pei; Wang, RuoNan; Lian, ZengYan
Abstract : In typical median and small aeroengines, the air used to realize the functions such as cooling of turbine blades and disks, sealing of turbine cavities and bearing chambers, adjusting of rotating assembly axial load is normally drawn through the rear cavity of centrifugal impeller, so the thorough understanding of flow characteristics and pressure distribution and the proposal of the corresponding control methods in the cavity are the key to design the rational secondary air system. With an impeller rear cavity in a small turbofan engine as an object, the current study was dedicated to the investigation of flow control methods in the cavity. Two methods, namely, baffle and swirl-controlled orifice, were proposed to regulate the pressure loss and distribution in the cavity. Furthermore, the influence of geometry parameters of the two methods such as the length of baffle, the space between the baffle and rotating disk wall, the orientation, and radial position of swirl-controlled orifice was investigated. The CFD results show that the swirl-controlled orifice which could deswirl the flow is more effective in regulating the pressure loss and its distribution in cavity than baffle. The variation of the radial position of the swirl-controlled orifice had little influence on pressure loss but obvious influence on pressure distribution; therefore, decreasing the radial position could reduce the axial load on the rotating disk without changing the outlet pressure.